Technology Transfer in Digital Era: Legal Environment - Bliznets, Ivan Anatol’yevich; Kartskhiya, Aleksandr Amiranovich; Smirnov, Mikhail Guramovich (Journal of History Culture and Art Research, 2018)
The spread of disruptive technology in the digital era is the ruling condition of modern sustainable development. The authors proceed from the fact that legal tools for the creation and use, protection of advanced technologies provide the technology transfer process from the owner to interested parties for further practical, commercial application or further improvement. The article analyzes the legal positions of the concept of technology, legal ways to use modern technologies, stages of their implementation and practical application. In the innovation process legal mechanism in combination with the modern means of innovative development stimulates the creation and transfer of new technologies and at the same time it is a key factor for sustainable development in the context of modern digital technology revolution. In the modern digital revolution, the technology transfer acquires new features and ways for the dissemination of technical innovation, which creates new challenges for legal theory and practice, and legal tools should meet the challenges of the time.